Current Issues of The Utilization of Online Dispute Resolution As A Method For International Trade Dispute Settlement - Nuzul Quraniati Rohmah (PT. Anagata Sembagi Education, 2024)
The transformation of international trade from conventional to digital impacts several things, including resolving international trade disputes. In order to realize an efficient and effective dispute resolution process, many countries have implemented ODR to settle international trade disputes. This study aims to analyze the implementation of ODR in various countries and examine issues with unclear guidelines based on international law. This research observes the development of ODR in Indonesia and the urgency for its implementation in Indonesia. The research is normative juridical, with a statutory and comparative approach. The results obtained in this study are model law arrangements relating to the standardization of ODR Providers aimed to protect the personal data of the parties, unification of ODR dispute resolution clauses, and formulation of national legal instruments to create legal certainty regarding ODR, including ODR proceedings, permits, and monitoring, as well as recognition and execution process of electronic ODR decisions.